Three new species of the genus Bodotria (Crustacea: Cumacea: Bodotriidae) from the Yellow Sea in Korea - Kim, Sung-Hyun; Lee, Chang-Mok; Kim, Young-Hyo (Zootaxa, 2020)
Three new species of Cumacea belonging to the genus Bodotria were collected from the Yellow Sea in Korea. Among them, Bodotria (Bodotria) hwanghaensis sp. nov. and Bodotria (Bodotria) pseudomaculosa sp. nov. share the dorso-lateral carina on the carapace and uniarticulated uropod endopod with other Korean Bodotria species. In contrast, the last one, Bodotria (Atlantobodotria) incarinata sp. nov. lacks the dorso-lateral carina on the carapace and has a biarticulated uropod endopod. The new species B. (A.) incarinata sp. nov. can be distinguished from all other Bodotria species by the combination of carapace without dorso-lateral carina or ridge, dorso-median carina marked over whole length of carapace, antero-lateral corner of carapace rounded, antennal notch shallow, maxilliped 3 merus and carpus dilated, pereopod 1 carpus not dilated, and pereopod 2 basis with plumose seta. The new species B. (B.) hwanghaensis sp. nov. can be distinguished from all other Bodotria species by the combination of carapace almost ovoid in dorsal view, carapace lower edge of mid-lateral depression forming a faint ridge, pereopod 1 carpus not dilated, and pereopod 2 basis without plumose seta. The new species B. (B.) pseudomaculosa sp. nov. can be distinguished from all other Bodotria species by the combination of carapace surface covered with coarse squamosa-reticulate patterning formed by large, shallow pits, carapace lower edge of mid-lateral depression forming an angular ridge, pereopod 1 carpus little dilated, and pereopod 2 basis with plumose seta. We described with full illustrations, including mouthparts for the three new species. Also, a key to the Korean Bodotria species is provided.